Ionic liquids and microwave irradiation as synergistic combination for polar Diels–Alder reactions using properly substituted heterocycles as dienophiles: A DFT study related - Mancini, Pedro Maximo Emilio (2012)
For the DA reactions between nitropyrrole derivatives and isoprene, the combination of microwave irradiation and protic ionic liquid, has a notable synergistic effect. DFT calculations suggest that a supplementary energy ranking in the IR region of 1700-1400 cm-1 can favour the structural changes in the reactants to reach the TS.